Fatores associados com a qualidade de vida e avaliação dos sintomas de ansiedade e depressão dos pacientes acromegálicos - Sá, Adriana Maria Guimarães (2017)
Acromegaly is a rare disease, often caused by a pituitary tumor that secretes excess growth hormone and is associated with enlarged extremities, multiple organ dysfunction, physical limitations, decreased daily productivity, social isolation and worsening of quality Of life (QOL). The objective of this study was to identify the factors associated with quality of life and to verify the association between psychopathological symptoms and quality of life in patients with acromegaly accompanied in the only reference service of neuroendocrinology in the State of Maranhão - Northeast Brazil. The Acro-Qol questionnaire, the inventories of Beck's anxiety and depression, and the cronbach alpha were calculated. In order to identify independently associated factors, multivariate linear regression was adjusted and to verify the relationship between the factors associated with psychopathological symptoms, Student's t test and calculated the pearson correlation coefficientto to verify the correlation between quality of life and levels of anxiety and depression. Values of p <0.05 were considered significant. The study sample is composed of 57 patients. Cronbach's alpha was observed from 0.7 in all domains of Acro-Qol. There was a predominance of female patients (63.2%), with a mean age of 53.52 ± 12.2 years, with a monthly income of 3.51 + 3.9 minimum wages, with a macroadenoma (72%) and undergoing surgery (59.6%). In the multivariate linear regression, there was a positive association of income with quality of life scores in all domains; (Β = 0.372, p = 0.004), physical (β = 0.988, p = 0.001), psychological (β = 0.342, p = 0.008) P = 0.012) and in those that were inserted in the labor market in the total domains (β = 0.288, p = 0.003), psychological (β = 0.291, p = 0.032) and personal relations (β = 0.314, p = 0.019). In Pearson's correlation, there was a negative association between quality of life scores and anxiety levels in all domains; (R = - 0.442, p = 0.001), physical (r = - 0.532, p = <0.001), psychological (r = - 0.357, p = 0.006) (R = -0.370, p = 0.005) and in depression levels also in all domains; (R = -0.421, p = 0.001), physical (r = -0.645, p = <0.001), psychological (r = -0.543, p = <0.001) And personal relationships (r = - 0.541, p = <0.001). In this population of acromegaly patients, coming from one of the less developed regions of Brazil, being in the labor market and having a higher income were related to better QoL and the more intense symptoms of anxiety and depression were related to worse quality of life. Patients who have a tumor in the pituitary even reaching control of the disease are subject to a premature increase of health risks. The challenge for the future is how to improve the outcome of pituitary patients, so they can be closer to the concept of achieving a better quality of life.